Pemanfaatan Kecerdasan Buatan Dalam Bisnis Digital Untuk Mendorong Inovasi Dan Keberlanjutan UMKM di Era Society 5.0 - Sri Devi, Apriandini; Veri, John (Sekolah Tinggi Teknologi Dumai, 2025)
This study aims to systematically examine the utilization of Artificial Intelligence (AI) in digital business to drive innovation and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the era of Society 5.0. A Systematic Literature Review (SLR) method was employed using the PRISMA approach to analyze relevant scientific literature published between 2021 and 2025. Analysis of 97 selected studies reveals that AI has significantly contributed to accelerating MSME digital transformation, particularly in product innovation, operational efficiency, and digital marketing strategies. Furthermore, AI plays a crucial role in helping MSMEs remain competitive and adaptive to market dynamics and technological developments. The study concludes that strategic and sustainable implementation of AI can serve as a key catalyst in shaping more innovative and competitive MSMEs in the digital era. Policy recommendations and capacity building are essential to fully harness the potential of AI for MSME development.